Is there any difference in the therapeutic effects of Levosimendan on advanced HFrEF patients with sinus rhythm or atrial fibrillation? - Wang, Wenyan; Li, Fawen; Huang, Huihui; Wu, Xin; Tian, Weixiang; Yu, Tao (Frontiers in Cardiovascular Medicine, 2023)
Patients with advanced heart failure have a high incidence of atrial fibrillation (AF) and develop into heart failure with reduced ejection fraction (HFrEF), and require higher doses of inotropes. However, it is uncertain about the differences in the effects of levosimendan in HFrEF patients with sinus rhythm or AF. A total of 63 advanced HFrEF subjects (ejection fraction < 40%) were divided into sinus rhythm (SR, n = 34) and atrial fibrillation (AF, n = 29) cohorts. All patients received six cycles of intermittent repeated levosimendan infusion. After 3 months of treatment, B-type natriuretic peptide (BNP), estimated glomerular filtration rate, resting heart rate (rHR), creatinine, left ventricle ejection fraction (LVEF), left ventricular end diastolic diameter and blood pressure body weight, NYHA classification were measured. After completing the course of treatment, LVEF, BNP, and rHR were significantly decreased (p < 0.0.5), and no significant differences between the two groups were observed (p > 0.05). The NYHA classification improved in the SR group but not in the AF group. There was no significant difference between patients with different rHRs (≤70 bpm vs. >70 bpm) in the SR group (p > 0.05) or in the AF group (rHR ≤ 90 bpm vs. rHR >90 bpm) (p > 0.05). This study showed no difference in the therapeutic effect of intermittent repeated levosimendan infusion on advanced HFrEF with different heart rhythms (SR or AF); Advanced HFrEF patients receive levosimendan treatment without taking the inference of heart rhythm.